Opening China: Karl F. A. Gützlaff and Sino-Western relations, 1827 - 1852 - Lutz, Jessie Gregory (Studies in the history of Christian missions, 2008)
The changing context of Sino-Western relations and Protestant missions, 1807-1860 -- Youth in a turbulent Germany and an expanding West -- Independent missionary -- The multiple roles of nineteenth-century missionaries -- The West learns about China : Gützlaff 's western-language writings -- Translating Christianity for China -- New horizons -- Karl Gützlaff and the Chinese union -- Gützlaff, Chinese Christians, and Chinese heterodox communities -- Karl Gützlaff : "Parson and pirate, Charlatan and genius